2020
DOI: 10.1080/09599916.2020.1720269
|View full text |Cite
|
Sign up to set email alerts
|

Performance metrics and required returns for UK real estate development schemes

Abstract: Real estate development has received less scrutiny than real estate investment in terms of appraisal practices and performance measurement. This is despite the inherent uncertainty and financial risks associated with development as an activity. We investigate market practices regarding performance metrics and return expectations both for residential and commercial real estate development in the UK, exploring what is considered as an appropriate return and how this varies according to type and duration of schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
6
6
0
Order By: Relevance
“…Crosby et al. (2018, 2020) and Coleman et al. (2012) found a similar result in surveying UK-based developers.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Crosby et al. (2018, 2020) and Coleman et al. (2012) found a similar result in surveying UK-based developers.…”
Section: Discussionsupporting
confidence: 59%
“…It was found that trader developers, and particularly residential developers, preferred non-cash flow ratio-based metrics such as MDC and RLV rather than the traditional DCF and NPV decision tools. Crosby et al (2018Crosby et al ( , 2020 and Coleman et al (2012) found a similar result in surveying UK-based developers. The typical cash flow pattern in projects by trader developers involves large capital outflows at the outset and throughout the construction stage, with large inflows upon practical completion.…”
Section: Conclusion 61 Summary Of Findingssupporting
confidence: 53%
See 1 more Smart Citation
“…These assertions imply that this asymmetric knowledge and understanding are held within the developer/landowner community and therefore bias the outcomes in ways that are not easy to prove. The fall in affordable housing provision by the seven major housebuilders between 2010 and 2017 from 40% to 19% of total completions while their average return on capital employed rose from under 7% to over 32% is suspicious but not incontrovertible (Crosby, et al, 2019). However, despite the lack of expertise generally within councils identified in the literature above and the concerns about viability and reducing developer contributions, one council faced with a number of these issues decided that "more needed to be done" (Quote from email from Islington Borough Council Planning Officer).…”
Section: Figure 1 Herementioning
confidence: 96%
“…Their results help researchers to find the best practical tools suitable for the field of study. Crosby, Devaney, and Wyatt (2020) have investigated market practices regarding performance metrics and return expectations both for residential and commercial real estate development in the UK, exploring what is considered to be appropriate return and how this varies according to the type and duration of the scheme and the method of appraisal used. The authors underline the uncertainty and financial risks associated with development as an activity.…”
Section: Croatian and Comparative Public Administrationmentioning
confidence: 99%